Aryl imine triazole polymer film as well as preparation method and application thereof
By introducing the aromatic imine triazole ring structure and specific preparation methods into the polymer film, the problem of low thermal conductivity of polymer films is solved, efficient thermal management and film stability are achieved, and it is suitable for high-tech fields.
Patent Information
- Application Number
- CN202411657503.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing polymer films have low thermal conductivity and heat dissipation performance, which limits their application in the high-tech field. The addition of traditional high-thermal fillers will lead to an increase in the film thickness, affecting the area size of micro electronic devices.
Arylimine triazole polymer films are used, which form hydrogen bonds and interspersed entanglement molecular chain structures by introducing benzene ring and triazole ring structures to improve thermal conductivity, and through specific preparation methods such as polycondensation reaction and imidation By reaction, a thin film with excellent high and low temperature resistance and thermal conductivity were prepared.
The thermal conductivity of the aromatic imine triazole polymer film is achieved to stabilize at room temperature and 200°C, meet the thermal management needs, while maintaining the lightness and flexibility of the film, and is suitable for high-tech fields.
Smart Images

Figure CN119161734A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polymers, and in particular to an aromatic imine triazole polymer film and a preparation method and application thereof. Background Art
[0002] As the operating frequency, integration and power density of electronic products continue to increase, effective thermal management is very urgent for electronic products. It is necessary to design an effective thermal management system to manage the accumulation of excessive heat generated. The main strategy of thermal management is to transfer the excess energy of electronic products to the outside through thermal conductive materials. Compared with traditional thermal management materials, thermal conductive films with high in-plane thermal conductivity have attracted greater attention as emerging candidate materials in the past decade and have shown great potential in thermal management applications of next-generation devices.
[0003] Polymer materials have shown great potential in solving the problem of thermal conductivity and heat dissipation, but the intrinsic thermal conductivity of polymer films is low, usually below 0.2 W / (m·K), which is much lower than that of materials such as metals, carbon and ceramics, which greatly limits the application of polymer films in high-tech fields. In order to solve the problem of thermal conductivity and heat dissipation of polymer films, work is mainly carried out from two aspects: one is to modify the matrix body, and the other is to use polymer films as the matrix and add high thermal conductivity fillers to the matrix. However, adding high thermal conductivity fillers will make the film thickness too high, affecting the area size of tiny electronic devices. Therefore, the design of intrinsic thermal conductive polymer films is very important.
[0004] Constructing an effective thermally conductive filler network and reducing phonon scattering at the interface are the main strategies for obtaining thermally conductive polymer composite films. All-carbon films have excellent thermal conductivity, light weight, and high flexibility, but the production temperature is high and the cost is high. Chinese patent CN118650939 A provides a method for preparing ultra-high thermal conductivity graphene sandwich composite films, with a thermal conductivity of 1600~2050 W / mk, but it is carbonized at 900~1200℃, which is high and not conducive to cost control. Chinese patent CN218197370 U provides a low thermal resistance thermally conductive insulating film, a first thermally conductive phase change layer, a thermally conductive silicone layer, a polyimide film, and a second thermally conductive phase change layer, which have low thermal resistance and good thermal conductivity, but the film thickness is relatively thick (0.02~0.06 mm), which is not conducive to application in certain fields. Patent CN115093565 B provides a polyphenylsulfone ether triazole with good high temperature resistance, proving the heat resistance of the triazole ring, but the film forming property is poor and cannot form a film. Therefore, it is of great research value to provide a new type of aromatic imine triazole with good high and low temperature resistance, thin thickness, good thermal conductivity and film forming property. Summary of the invention
[0005] The object of the present invention is to provide an aryl imine triazole polymer film and a preparation method and application thereof. The aryl imine triazole polymer film not only has excellent high and low temperature resistance, but also has good film-forming performance and thermal conductivity, and is thin (2-200 mm).
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides an aryl imine triazole polymer film, wherein the aryl imine triazole polymer in the aryl imine triazole polymer film has a structure shown in Formula I: Formula I; In Formula I, R includes or ; Ar includes ; n=21~100 and n is an integer.
[0007] Preferably, n=21~35 and n is an integer.
[0008] Preferably, the weight average molecular weight Mw of the aromatic imine triazole polymer is 15,000-350,000.
[0009] The present invention provides a method for preparing the aromatic imine triazole polymer film described in the above technical solution, comprising the following steps: A diamine monomer having a structure shown in Formula II and a dianhydride monomer having a structure shown in Formula III are mixed with an organic solvent to carry out a polycondensation reaction to obtain a polyamic acid; The polyamic acid, the catalyst and the dehydrating agent are mixed to carry out imidization reaction to obtain an aromatic imide triazole polymer; The aryl imine triazole polymer is mixed with an organic solvent, the obtained solution is placed on a substrate, a gradient temperature program is performed, and then the solution is peeled off and dried to obtain an aryl imine triazole polymer film; Formula II; Formula III; In formula II, R includes or , in formula III, Ar includes .
[0010] Preferably, the molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.05).
[0011] Preferably, the polycondensation reaction is carried out at a temperature of 0 to 80° C. and for a time of 5 to 7 h.
[0012] Preferably, the dehydrating agent includes anhydrous acetic acid, anhydrous benzoic acid, anhydrous phenolic acid, acetic anhydride, propylene glycol or phosphorus trichloride; the catalyst includes benzyltriethylammonium chloride, tetrabutylammonium bromide, dimethylamine, pyrrole, triethylamine, pyridine or isoquinoline.
[0013] Preferably, the molar ratio of the diamine monomer, the dehydrating agent and the catalyst is (0.2-1):1:(0.2-1); the temperature of the imidization reaction is 25-300° C., and the time is 1-10 h.
[0014] Preferably, the temperature range of the gradient heating is 60-250° C., and the treatment time is 6-16 hours.
[0015] The present invention provides application of the aromatic imine triazole polymer film described in the above technical solution in a thermal conductive film.
[0016] The aromatic imide triazole polymer film of the present invention contains a skeleton structure of a benzene ring and a triazole ring, which gives it good thermal stability and mechanical strength. The strong imide bond and the triazole ring have high thermal stability, which gives it high and low temperature resistance. The introduction of the triazole ring constructs hydrogen bonding between polymer chain segments, so that the polymer chain forms a relatively orderly structure, forms an interlaced and entangled structure between molecular chains, and constructs hydrogen bonding between side groups, so that the curled molecular chain presents a stretched state, improves the orderliness of chain segment aggregation, and creates a phonon transmission path, thereby improving the film-forming property and intrinsic thermal conductivity (thermal conductivity) of the aromatic imide triazole.
[0017] The Tg (glass transition temperature) of the aryl imine triazole polymer film provided by the present invention is 254-270°C, and the Td10% (10% thermal weight loss temperature in nitrogen) reaches 621.8-664.2°C. In addition, the mechanical properties at -196°C and 25°C show significant temperature invariance, proving that the aryl imine triazole polymer film not only has good high and low temperature resistance, but also has good mechanical properties. At the same time, the thermal conductivity of aryl imine triazole at room temperature is 0.45-0.62 W·(m·K) -1 , the thermal conductivity at 200°C is 0.43~0.6 W·(m·K) -1 , not only has good thermal performance, but also has good thermal conductivity at room temperature and 200°C, and the thermal conductivity stability at a high temperature of 200°C can meet the thermal management requirements in many cases. Therefore, the aromatic imine triazole polymer film provided by the present invention not only has better high and low temperature resistance, but also has good mechanical properties and thermal conductivity.
[0018] The preparation method of the invention is to efficiently prepare the diamine monomer and the dianhydride monomer through a condensation reaction, with mild reaction conditions and high reaction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is an infrared comparison image of the diamine monomer Diamine-1 prepared in Example 1 and its raw materials; Figure 2 This is an infrared comparison image of PTAI-1 prepared in Example 1 and its raw materials; Figure 3 This is an infrared comparison image of the diamine monomer Diamine-2 prepared in Example 2 and its raw materials; Figure 4 This is an infrared comparison image of PTAI-2 prepared in Example 2 and its raw materials; Figure 5 The DSC graphs of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2; Figure 6 Thermogravimetric diagrams of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2; Figure 7 Graph showing stress-strain data of the PTAI-1 film prepared in Example 1 and the PTAI-2 film prepared in Example 1; Figure 8 The thermal conductivity data graph of the PTAI-1 film prepared in Example 1 and the PTAI-2 film prepared in Example 1. DETAILED DESCRIPTION
[0020] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0021] The present invention provides an aryl imine triazole polymer film, wherein the aryl imine triazole polymer in the aryl imine triazole polymer film has a structure shown in Formula I: Formula I; In Formula I, R includes or ; Ar includes ; n=21~100 and n is an integer.
[0022] In the present invention, n=21-35 and n is an integer, more preferably 26-28.
[0023] In the present invention, the weight average molecular weight Mw of the aromatic imine triazole polymer is 15000-350000.
[0024] In the present invention, the aromatic imine triazole polymer is preferably
[0025] or
[0026] The present invention provides a method for preparing the aromatic imine triazole polymer film described in the above technical solution, comprising the following steps: A diamine monomer having a structure shown in Formula II and a dianhydride monomer having a structure shown in Formula III are mixed with an organic solvent to carry out a polycondensation reaction to obtain a polyamic acid; The polyamic acid, the catalyst and the dehydrating agent are mixed to carry out imidization reaction to obtain an aromatic imide triazole polymer; The aromatic imine triazole polymer is mixed with an organic solvent, the obtained solution is placed on a substrate, a gradient temperature program is performed, and then the solution is peeled off and dried to obtain an aromatic imine triazole polymer film; Formula II; Formula III; In formula II, R includes or , in formula III, Ar includes .
[0027] In the present invention, the preparation method of the diamine monomer having the structure shown in Formula II is preferably to mix a 4,4'-diazide compound, m-aminophenylacetylene, a catalyst and an organic solvent under nitrogen conditions, and perform a click polymerization reaction to obtain a diamine monomer; the 4,4'-diazide compound is preferably 4,4'-diazide diphenyl sulfone or 4,4'-diazide diphenyl ether. The 4,4'-diazide diphenyl sulfone or 4,4'-diazide diphenyl ether is prepared according to the method disclosed in patent CN 118684885 A.
[0028] In the present invention, the molar ratio of the 4,4'-diazide compound to m-aminophenylacetylene is preferably 1:(1.5-3), more preferably 1:2.
[0029] In the present invention, the catalyst is preferably copper sulfate pentahydrate and sodium ascorbate; the molar ratio of the 4,4'-diazide compound to copper sulfate pentahydrate and sodium ascorbate is preferably 0.01:0.005:0.01.
[0030] In the present invention, the organic solvent used in the click polymerization reaction is preferably N,N-dimethylacetamide; the present invention has no special limitation on the amount of the organic solvent used, and the amount can be adjusted according to actual needs to ensure the smooth progress of the reaction.
[0031] In the present invention, the temperature of the click polymerization reaction is preferably 50-70° C., more preferably 60° C., and the time is preferably 5-7 h, more preferably 6 h.
[0032] After the click polymerization reaction is completed, the present invention preferably drops the obtained product into a stirred saturated disodium ethylenediaminetetraacetic acid aqueous solution to obtain a light yellow precipitate, which is filtered out and freeze-dried to obtain a diamine monomer.
[0033] In the present invention, the dianhydride monomer having the structure shown in Formula III is preferably 4,4'-oxydiphthalic anhydride.
[0034] In the present invention, the molar ratio of the diamine monomer to the dianhydride monomer is preferably 1:(1-1.05), more preferably 1:(1-1.02).
[0035] The organic solvent used in the polycondensation reaction is preferably N,N-dimethylacetamide ; The present invention has no particular limitation on the amount of the organic solvent used, and the amount can be adjusted according to actual needs to ensure that the reaction proceeds smoothly.
[0036] In the present invention, the diamine monomer is preferably dissolved in an organic solvent, and then the dianhydride monomer is added three times in equal portions to carry out a polycondensation reaction.
[0037] In the present invention, the temperature of the polycondensation reaction is preferably 0-80° C., more preferably 5-50° C., and the time is preferably 5-7 h, more preferably 6 h; the polycondensation reaction is preferably carried out in an ice bath.
[0038] After the polycondensation reaction, the present invention preferably does not perform any treatment, but directly adds a dehydrating agent and a catalyst to the obtained product solution to perform an imidization reaction (chemical imidization dehydration).
[0039] In the present invention, the dehydrating agent preferably includes anhydrous acetic acid, anhydrous benzoic acid, anhydrous phenolic acid, acetic anhydride, propylene glycol or phosphorus trichloride; the catalyst preferably includes benzyltriethylammonium chloride, tetrabutylammonium bromide, dimethylamine, pyrrole, triethylamine, pyridine or isoquinoline; the molar ratio of the diamine monomer, the dehydrating agent and the catalyst is preferably (0.2~1):1:(0.2~1), more preferably 0.5:1:0.5.
[0040] In the present invention, the temperature of the imidization reaction is preferably 25-300° C., more preferably 200° C., and the time is preferably 1-10 h, more preferably 4 h.
[0041] After the imidization reaction is completed, the present invention preferably adds the obtained product dropwise into rapidly stirred deionized water, collects the precipitate by suction filtration with water, and freeze-dries it for 24 hours to obtain an aromatic imine triazole polymer.
[0042] After obtaining the aryl imine triazole polymer, the present invention mixes the aryl imine triazole polymer with an organic solvent, places the obtained solution on a substrate, performs a gradient temperature increase procedure, and then peels and dries to obtain an aryl imine triazole polymer film.
[0043] The present invention preferably dissolves the aryl imine triazole polymer in an organic solvent (preferably N,N-dimethylacetamide) to obtain a polymer solution with a concentration of 10-15wt% (more preferably 13wt%), spreads the polymer solution on a clean glass sheet by a casting method or a film drawing method, cools to room temperature after a gradient temperature increase program, soaks the glass sheet in deionized water, peels and dries, and obtains an aryl imine triazole polymer film.
[0044] In the present invention, the thickness of the aromatic imine triazole polymer film is preferably 2 to 200 mm, more preferably 5.2 to 5.8 mm.
[0045] In the present invention, the temperature range of the gradient heating is preferably 60-250°C, and the treatment time is preferably 6-16h; the gradient heating program is more preferably 60°C / 12 h, 80°C / 2 h, 100°C / 1 h, 200°C / 1 h.
[0046] The present invention provides the application of the aromatic imine triazole polymer described in the above technical solution in a thermal conductive film. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] This example provides the preparation of an aromatic imine triazole polymer film: (1) Add 0.01 mol of 4,4'-diazide diphenyl sulfone (prepared according to patent CN 118684885 A) and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask protected by nitrogen gas and a magnetic stirring heating device, add 0.02 mol of m-aminophenylacetylene after dissolution, and then add 0.005 mol of copper sulfate pentahydrate and 0.01 mol of sodium ascorbate in sequence, heat and stir at 60°C, react for 6 h, and after the reaction is completed, drop the obtained product solution into a stirred saturated disodium ethylenediaminetetraacetic acid aqueous solution to obtain a light yellow precipitate, filter and freeze-dry to obtain the diamine monomer Diamine-1; (2) Add 0.01 mol of diamine monomer Diamine-1 and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask protected by nitrogen gas and a magnetic stirring heating device. After stirring at room temperature to dissolve, add 0.0102 mol of 4,4'-oxydiphthalic anhydride in three times under an ice bath, continue to react at 5°C for 6 h, add 0.02 mol of dehydrating agent acetic anhydride and 0.01 mol of catalyst triethylamine, stir at 25°C for 4 h, pour the resulting solution into deionized water for precipitation, filter and wash with deionized water for 3 times until the pH value of the filtrate is 7, and dry the resulting precipitate in a freeze dryer for 24 h to obtain an aromatic imine triazole polymer PTAI-1, the structural formula of which is shown below; (3) PTAI-1 was dissolved in N,N-dimethylacetamide to obtain a viscous solution with a concentration of 13 wt%, which was poured onto a clean glass plate by a casting method. After a gradient heating program of 60℃ / 12 h, 80℃ / 2 h, 100℃ / 1 h, and 200℃ / 1 h, the glass plate was immersed in deionized water after reaching room temperature. After peeling and drying, a PTAI-1 film with a thickness of 5.2 mm was obtained.
[0050]
[0051] Example 2
[0052] This example provides the preparation of an aryl imine triazole polymer film: (1) Add 0.01 mol of 4,4'-diazide diphenyl ether (prepared according to patent CN 118684885 A) and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask protected by nitrogen gas and a magnetic stirring heating device, add 0.02 mol of m-aminophenylacetylene after dissolution, and then add 0.005 mol of copper sulfate pentahydrate and 0.01 mol of sodium ascorbate in sequence, heat and stir at 60°C, react for 6 h, and after the reaction is completed, drop the obtained product solution into a stirred saturated disodium ethylenediaminetetraacetic acid aqueous solution to obtain a light yellow precipitate, filter and freeze-dry to obtain the diamine monomer Diamine-2; (2) Add 0.01 mol of diamine monomer Diamine-2 and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask protected by nitrogen gas and a magnetic stirring heating device. After stirring at room temperature to dissolve, add 0.0102 mol of 4,4'-oxydiphthalic anhydride in three times under an ice bath, continue to react at 5°C for 6 hours, add 0.02 mol of dehydrating agent acetic anhydride and 0.01 mol of catalyst triethylamine, stir at 25°C for 4 hours, pour the resulting solution into deionized water for precipitation, filter and wash with deionized water for 3 times until the pH value of the filtrate is 7, and dry the resulting precipitate in a freeze dryer for 24 hours to obtain an aromatic imine triazole polymer PTAI-2, the structural formula of which is shown below; (3) PTAI-2 was dissolved in N,N-dimethylacetamide to obtain a viscous solution with a concentration of 13 wt%, which was poured onto a clean glass plate by a casting method. After a gradient temperature increase program of 60°C / 12 h, 80°C / 2 h, 100°C / 1 h, and 200°C / 1 h, the glass plate was immersed in deionized water after reaching room temperature. After peeling and drying, a PTAI-2 film with a thickness of 5.8 mm was obtained.
[0053]
[0054] Characterization Figure 1 This is an infrared comparison of the diamine monomer Diamine-1 prepared in Example 1 and its raw materials; wherein a is 4,4'-diazide diphenyl sulfone, b is m-aminophenyl acetylene, and c is Diamine-1. Figure 1 It can be seen that the 3286 cm -1 and 2113cm -1 The absorption peaks of C≡CH and -N3 disappeared at 3129 cm -1 The characteristic vibration absorption peak of -CH on the triazole ring appears at 3400 cm -1 The double peaks of amino groups appeared nearby, verifying the successful preparation of diamine monomer Diamine-1.
[0055] Figure 2 This is an infrared comparison of PTAI-1 prepared in Example 1 and its raw materials; wherein a is Diamine-1, b is 4,4-oxydiphthalic anhydride, and c is PTAI-1. Figure 2 It can be seen that at the wave number 1774 cm -1 and 1713 cm -1 The asymmetric and symmetric stretching peaks of the carbonyl group (-C=O) on the imide ring appeared at 1367 cm -1 The peak is attributed to the -CN stretching peak on the imide ring, 746 cm-1 The absorption peak at 1593 cm-1 is attributed to the bending vibration of -C=O on the imide ring. -1 The characteristic peak of polyamide acid is 1710 cm -1 (Stretching vibration peak of carboxyl-CO), 1660 cm -1 (amide CO), 1550 cm -1 (Amide CN) was absent, indicating that the imidization was basically complete, and it was preliminarily judged that PTAI-1 was successfully prepared.
[0056] Figure 3 This is an infrared comparison of the diamine monomer Diamine-2 prepared in Example 2 and its raw materials; wherein a is 4,4'-diazide diphenyl ether, b is m-aminophenylacetylene, and c is Diamine-2. Figure 3 It can be seen that the 3286 cm -1 and 2122cm -1 The absorption peaks of C≡CH and -N3 disappeared at 3123 cm -1 The characteristic vibration absorption peak of -CH on the triazole ring appears at 3400 cm -1 The double peaks of amino groups appeared nearby, verifying the successful preparation of diamine monomer Diamine-1.
[0057] Figure 4 This is an infrared comparison of PTAI-2 prepared in Example 2 and its raw materials; wherein a is Diamine-2, b is 4,4-oxydiphthalic anhydride, and c is PTAI-2. Figure 4 It can be seen that at the wave number 1774 cm -1 and 1713 cm -1 The asymmetric and symmetric stretching peaks of the carbonyl group (-C=O) on the imide ring appeared at 1367 cm -1 The peak is attributed to the -CN stretching peak on the imide ring, 746 cm -1 The absorption peak at 1593 cm-1 is attributed to the bending vibration of -C=O on the imide ring. -1 The characteristic peak of polyamide acid is 1710 cm -1 (Stretching vibration peak of carboxyl-CO), 1660 cm -1 (amide CO), 1550 cm -1 (Amide CN) does not exist, indicating that the imidization is basically complete, and it is preliminarily judged that PTAI-2 is successfully prepared.
[0058] Performance Testing (1) Determination of molecular weight and distribution coefficient The molecular weight and distribution coefficient of PTAI-1 and PTAI-2 provided in Examples 1 and 2 were measured, and the results are shown in Table 1.
[0059] Table 1 Molecular weight and distribution coefficient of PTAI-1 and PTAI-2 provided in Examples 1 and 2
[0060] As can be seen from Table 1, both PTAI-1 and PTAI-2 have relatively high molecular weight and narrow molecular weight distribution, and have the conditions for film formation.
[0061] (2) Viscosity test The viscosity of PTAI-1 and PTAI-2 provided in Examples 1 and 2 was tested, and the intrinsic viscosity of the polymer solution was measured using an Ubbelohde viscometer. N,N-dimethylacetamide (DMAc) was used as the solvent, the initial concentration of the polymer solution was 15 wt%, and the test temperature was set at 25°C. The results are shown in Table 2.
[0062] Table 2 Intrinsic viscosity of PTAI-1 and PTAI-2 provided in Examples 1 and 2
[0063] It can be seen from Table 2 that in the systems of PTAI-1 and PTAI-2, the intermediate polyamic acid PAA has a relatively high intrinsic viscosity value, which provides the possibility for subsequent film formation.
[0064] (3) Thermal performance test The thermal properties of PTAI-1 and PTAI-2 provided in Examples 1 and 2 were tested. The DSC test process and conditions were: heating from 40°C to 300°C at a heating rate of 10°C / min, then cooling to 40°C at a heating rate of 30°C / min, and finally heating to 250°C at a heating rate of 10°C / min.
[0065] The thermogravimetric test was carried out in a nitrogen atmosphere with a protective gas flow rate of 30 mL / min and a purge gas flow rate of 30 ml / min. The temperature was increased from 40°C to 600°C at a heating rate of 10°C / min to obtain a thermogravimetric spectrum of the sample.
[0066] Figure 5 The DSC graphs of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2; Figure 6 The thermogravimetric diagrams of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2.
[0067] Table 3 Thermal performance test results of PTAI-1 and PTAI-2
[0068] from Figure 5 , Figure 6 As shown in Table 3, PTAI-1 and PTAI-2 have better high temperature resistance.
[0069] (4) High and low temperature performance test The high and low temperature performance of the PTAI-1 membrane and the PTAI-2 membrane prepared in Examples 1 and 2 were tested by a universal testing machine.
[0070] The film was cut into dumbbell-shaped specimens according to GBT 1040-92. The tensile rate was set to 10 mm / min. The tensile tests were carried out at -196℃ and 25℃ respectively. The test results are shown in Figure 7 .
[0071] Figure 7 The stress-strain data diagram of the PTAI-1 film prepared in Example 1 and the PTAI-2 film prepared in Example 2 is shown in FIG. Figure 7 As shown, at -196℃ and 25℃, the film exhibits significant temperature-invariant mechanical properties, which is very important for applications in extreme environments. This proves that the film's mechanical properties are not greatly affected by extreme temperatures and can be used in extremely cold conditions.
[0072] (5) Thermal conductivity test The thermal conductivity of the PTAI-1 film and the PTAI-2 film provided in Examples 1 and 2 was tested by annealing at room temperature 25°C and 200°C for 1 hour. Figure 8 As shown, after annealing, the change in thermal conductivity is within the experimental error range, and the thermal conductivity stability at 200°C can meet the thermal management requirements in many cases.
[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An aromatic imine triazole polymer film, characterized in that: The aryl imine triazole polymer in the aryl imine triazole polymer film has a structure shown in Formula I: Formula I; In Formula I, R includes or ; Ar includes ; n=21~100 and n is an integer.
2. The aryl imine triazole polymer film according to claim 1, characterized in that: n=21~35 and n is an integer.
3. The aryl imine triazole polymer film according to claim 1, characterized in that: The weight average molecular weight Mw of the aromatic imine triazole polymer is 15000-350000.
4. The method for preparing the aryl imine triazole polymer film according to any one of claims 1 to 3, characterized in that: The following steps are involved: A diamine monomer having a structure shown in Formula II and a dianhydride monomer having a structure shown in Formula III are mixed with an organic solvent to carry out a polycondensation reaction to obtain a polyamic acid; The polyamic acid, the catalyst and the dehydrating agent are mixed to carry out imidization reaction to obtain an aromatic imide triazole polymer; The aryl imine triazole polymer is mixed with an organic solvent, the obtained solution is placed on a substrate, a gradient temperature program is performed, and then the solution is peeled off and dried to obtain an aryl imine triazole polymer film; Formula II; Formula III; In formula II, R includes or , in formula III, Ar includes .
5. The preparation method according to claim 4, characterized in that: The molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.05).
6. The preparation method according to claim 5, characterized in that: The temperature of the polycondensation reaction is 0-80°C and the time is 5-7 h.
7. The preparation method according to claim 4, characterized in that: The dehydrating agent includes anhydrous acetic acid, anhydrous benzoic acid, anhydrous phenolic acid, acetic anhydride, propylene glycol or phosphorus trichloride; the catalyst includes benzyltriethylammonium chloride, tetrabutylammonium bromide, dimethylamine, pyrrole, triethylamine, pyridine or isoquinoline.
8. The preparation method according to claim 7, characterized in that: The molar ratio of the diamine monomer, the dehydrating agent and the catalyst is (0.2-1):1:(0.2-1); the temperature of the imidization reaction is 25-300° C., and the time is 1-10 h.
9. The preparation method according to claim 4, characterized in that: The temperature range of the gradient heating is 60-250° C., and the treatment time is 6-16 hours.
10. Use of the aryl imine triazole polymer film according to any one of claims 1 to 3 or the aryl imine triazole polymer film prepared by the preparation method according to any one of claims 4 to 9 in a thermal conductive film.
Citation Information
Patent Citations
Polyamine containing triazole ring and preparation method and application thereof
CN101774973A
Novel polytriazoles imide resin and preparation method thereof
CN101775138A
Aryl ether imide polytriazole as well as preparation method and application thereof
CN118684885A
Cited By
A quaternized triazole imide polymer, its preparation method and application, a quaternized triazole imide battery separator and its application
CN119955096B
